2020
DOI: 10.1186/s40623-020-01238-7
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced wide-area multi-GNSS RTK and rapid static positioning in the presence of ionospheric disturbances

Abstract: Ionospheric disturbances are the phenomena which adversely affect the performance of precise positioning. This holds true even for multi-constellation relative positioning supported with network-derived ionospheric corrections. In such scenario the unfavorable effect is caused by a poor accuracy of corrections, which, in turn, is driven by the deterioration of the spatial interpolation process. The positioning becomes even more challenging in a wide-area scenario with baselines over 100 km. In this paper, we a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 49 publications
1
3
0
Order By: Relevance
“…That finding is especially evident for the ROTI time series during the storm of August 2018, since the southern stations exhibit several times higher ROTI than the northern ones and reach values even higher than those during the St. Patrick's Day storm. The reason for such strong amplification of ROTI during the main phase of the storm in 2018 is the occurrence of small and medium irregularities resulting from auroral precipitation and the position of the latter directly above the test network (Paziewski and Sieradzki, 2020). The detailed analysis of ionospheric conditions given in that study confirmed that the polar part of the ionosphere was relatively quiet in this case.…”
Section: Analysis Of Roti and Vtec Values At The Gnss Permanent Stati...supporting
confidence: 54%
See 1 more Smart Citation
“…That finding is especially evident for the ROTI time series during the storm of August 2018, since the southern stations exhibit several times higher ROTI than the northern ones and reach values even higher than those during the St. Patrick's Day storm. The reason for such strong amplification of ROTI during the main phase of the storm in 2018 is the occurrence of small and medium irregularities resulting from auroral precipitation and the position of the latter directly above the test network (Paziewski and Sieradzki, 2020). The detailed analysis of ionospheric conditions given in that study confirmed that the polar part of the ionosphere was relatively quiet in this case.…”
Section: Analysis Of Roti and Vtec Values At The Gnss Permanent Stati...supporting
confidence: 54%
“…Respective research on this topic was conducted, for example, by Wanninger (Wanninger, 2004), who proposed to use the I95 index that provides statistical information to support RTK and N-RTK, and by Park et al (Park et al, 2017), who refined the stochastic model of RTK positioning and exploited Total Electron Content (TEC) maps. The feasibility of precise long-range positioning with an enhanced RTK model under the ionospheric disturbance was reported in (Sieradzki and Paziewski, 2016;Paziewski and Sieradzki, 2020). Additionally, Vadakke Veettil et al (Vadakke Veettil et al, 2020) refined the stochastic model of DF PPP to meet the challenges of GNSS positioning in the ionospheric scintillation environment.…”
Section: Introductionmentioning
confidence: 99%
“…With this rapid development of GNSS, multi-GNSS and multi-frequency Precise Point Positioning (PPP) and Real-Time Kinematic (RTK) technologies have IOP Publishing doi:10.1088/1755-1315/1127/1/012006 2 been extensively researched to enable high-precision positioning [2,3]. Positioning accuracy in RTK mode can also be improved to centimeter levels, for example by using dual antennas with baseline constraint vector [4], utlilize multi-station RTK and rate of TEC correction [5], or enhance strategy to determine stochastic model of observation [6]. Besides that, there has been a solution to reduce the cost of GNSS observation through the increasing availability of low-cost GNSS in recent years.…”
Section: Introductionmentioning
confidence: 99%
“…RTK can effectively weaken ionospheric and tropospheric delay errors, eliminate errors such as hardware delays at the satellite and receiver, maintain whole-cycle characteristics of ambiguity, and provide centimeter-level solution results with good satellite visibility [4][5][6][7]. In addition, RTK can realize high-precision positioning in low-cost terminals such as smartphones, providing smartphone users with centimeterlevel positioning in outdoor environments [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%